Chapter 10. Minor Vegetable Crop Production - Dakshina R. Seal; Qingren Wang; Ramdas Kanissery; Anna Meszaros; Crystal A. Snodgrass; Julien Beuzelin; Johan Desaeger; Nicholas S. Dufault; Katia Viana Xavier; Shouan Zhang (EDIS)
Chapter 10 of the Vegetable Production Handbook of Florida